1983
DOI: 10.1063/1.93790
|View full text |Cite
|
Sign up to set email alerts
|

Spectral dependence of reversible optically induced transitions in organometallic compounds

Abstract: Optical switching in the class of semiconducting organometallic films such as copper and silver tetracyanoquinodimethane (CuTCNQ and AgTCNQ) can be erased using CO2 laser radiation. The effect can be observed by Raman spectroscopy and direct observation. Results on the wavelength and irradiance dependence of the optical switching threshold are also presented and interpreted in light of proposed switching mechanisms in these organic materials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(27 citation statements)
references
References 11 publications
0
27
0
Order By: Relevance
“…Potember, Cowan, and co-workers have discovered a switching and/or memory effect in the fully ionic anion radical salts of TCNQ derivatives by electric field application 738 or laser irradiation. 739 Anion radical salts of TCNQ analogues with strong electron accepting ability, such as F 4 TCNQ and TNAP, exhibited both switching (from high-resistive state to highconductive state) and memory effects (termed as memory switching; the lower double well potential in Fig. 78b), while the salts with weak acceptors such as TCNQ exhibited only the switching effect (termed as threshold switching; the upper double well potential in Fig.…”
Section: Band Fillingmentioning
confidence: 99%
See 2 more Smart Citations
“…Potember, Cowan, and co-workers have discovered a switching and/or memory effect in the fully ionic anion radical salts of TCNQ derivatives by electric field application 738 or laser irradiation. 739 Anion radical salts of TCNQ analogues with strong electron accepting ability, such as F 4 TCNQ and TNAP, exhibited both switching (from high-resistive state to highconductive state) and memory effects (termed as memory switching; the lower double well potential in Fig. 78b), while the salts with weak acceptors such as TCNQ exhibited only the switching effect (termed as threshold switching; the upper double well potential in Fig.…”
Section: Band Fillingmentioning
confidence: 99%
“…Switching and memory phenomena observed in several TCNQ materials, 224,[738][739][740] and photo-induced phase transition (PIPT) observed in the DA system near the N-I boundary (see section 3.1.3), 218,224 TCNQ, 741 EDO, 428 and DCNQI salts 742,743 also belong to this strategy. The PIPT is a characteristic cooperative phenomenon of a strongly coupled electron and phonon (or molecular vibration) system.…”
Section: Band Fillingmentioning
confidence: 99%
See 1 more Smart Citation
“…The forward reaction has been shown to be independent of the wavelength of the incident optical irradiation, and optical switching has been observed at energies above and below band gap of AgTCNQ (0.3 ev) [6]. The reaction shown in Eq.…”
Section: Introductionmentioning
confidence: 96%
“…[ 1–5 ] CuTCNQ, as one of the typical CT complexes, have been widely researched around 40 years due to its intriguing structural, optoelectronic properties. [ 6–23 ] Since Potember et al reported bistable, reproducible electrical switching of CuTCNQ in 1979, [ 6 ] plenty of studies about this CT complex have been done, particularly on its synthesis and corresponding device performance. However, up to now, it is still not clear about the switching mechanism of CuTCNQ devices, although various attempts have been conducted for the exploration of the switching mechanism.…”
Section: Introductionmentioning
confidence: 99%